Solidaritas Anarkisme Suporter Bola PSIM DAN PSS - Werdiyanti, Tera Puspita; Noor, As Martadani; Paharizal, Rizal (Universitas Widya Mataram, 2019)
This research is located in Sleman, Yogyakarta. This research was conducted when researcher saw the solidarity of anarchism of football supporters. Factors related to the solidarity of anarchism of football supporters and the empowerment of football supporters, especially with PSIM and PSS. This research wants to describe more clearly how the solidarity of anarchism is, the factors associated with solidarity of anarchism and the empowerment of suporter in PSIM and PSS football clubs. This research was conducted with a qualitative descriptive research method. Data was collected by Snow Ball sampling until the data was at its saturation point. This method was chosen because the number of actors is large so itÂ could gets more accurate data. The results obtained in the solidarity of football supporters anarchism prove that there are improvements from the supporters. Then the factors related to the solidarity of anarchism are still trying to become supporters who are more loved by the community and the empowerment of PSIM and PSS footballÂ supporters has not received training from any party.